Effect of curcumin on hippocampus dentate gyrus injury induced by nicotine in rats - Cyrus Jalili; Babak Arji Rodsari; Shiva Roshankhah; Mohammad Reza Salahshoor (Shahrekord University of Medical Sciences, 2019)
Introduction: Nicotine is the most important alkaloid compound in tobacco and is a major risk factor in the development of functional disorder of several organ systems. Some plants produce Curcumin, which has antioxidant and neuroprotective properties. This study was designed to evaluate the therapeutic effects of curcumin against nicotine injury on the hippocampus CA1 region of rats.Methods: In this study, 48 male Wistar rats were randomly assigned to eight groups: Normal control (saline) group, Nicotine control group (0.5 mg/kg); Curcumin groups (10, 30, and 60 mg/kg) and Nicotine + Curcumin groups (10, 30, and 60 mg/kg). Treatments were administered intraperitoneally daily for 28 days. Golgi staining technique investigated the number of dendritic spines. Cresyl violet staining method was used to determine the number of neurons in hippocampal region CA1. Griess technique was assessed to determine serum nitrite oxide level. Also, the Ferric reducing/antioxidant power (FRAP) method was applied to determine the total antioxidant capacity.Results: Nicotine administration significantly increased nitrite oxide level and decreased total antioxidant capacity as well as the number of neuronal dendritic spines and neurons compared to the normal control group (P < 0.01). In all Curcumin and Nicotine + Curcumin groups, the number of neurons, neuronal dendritic spines, and total antioxidant capacity increased significantly compared to the nicotine control group, while nitrite oxide level decreased significantly compared to the nicotine control group (P < 0.01).Conclusion: Curcumin administration can improve hippocampal CA1 region injury induced by nicotine.